Limited genetic and antigenic diversity within parasite isolates used in a live vaccine against Theileria parva. Issue 8 (July 2016) - Hemmink, Johanneke D.; Weir, William; MacHugh, Niall D.; Graham, Simon P.; Patel, Ekta; Paxton, Edith; Shiels, Brian; Toye, Philip G.; Morrison, W. Ivan; Pelle, Roger
Graphical abstract: Highlights: Genotyping and gene sequencing reveal limited diversity in a live Theileria parva vaccine. Two of the vaccine components show a high level of similarity at all loci. The vaccine contains very little of the diversity found in field T. parva. The vaccine is suboptimal for generating immunity again diverse parasite strains. The presence of minor genotypic components poses difficulties for quality control. Abstract: An infection and treatment protocol is used to vaccinate cattle against Theileria parva infection. Due to incomplete cross-protection between different parasite isolates, a mixture of three isolates, termed the Muguga cocktail, is used for vaccination. While vaccination of cattle in some regions provides high levels of protection, some animals are not protected against challenge with buffalo-derived T. parva . Knowledge of the genetic composition of the Muguga cocktail vaccine is required to understand how vaccination is able to protect against field challenge and to identify the potential limitations of the vaccine. The aim of the current study was to determine the extent of genetic and antigenic diversity within the parasite isolates that constitute the Muguga cocktail. High throughput multi-locus sequencing of antigen-encoding loci was performed in parallel with typing using a panel of micro- and mini-satellite loci. The former focused on genes encoding CD8 + T cell antigens, believed to be relevant to protective immunity. The results demonstrate that each of the three component stocks of the cocktail contains limited parasite genotypic diversity, with single alleles detected at many gene/satellite loci and, moreover, that two of the components show a very high level of similarity. Thus, the vaccine incorporates very little of the genetic and antigenic diversity observed in field populations of T. parva . The presence of alleles at low frequency (<10%) within vaccine component populations also points to the possibility of variability in the content of vaccine doses and the potential for loss of allelic diversity during tick passage. The results demonstrate that there is scope to modify the content of the vaccine in order to enhance its diversity and thus its potential for providing broad protection. The ability to accurately quantify genetic diversity in vaccine component stocks will facilitate improved quality control procedures designed to ensure the long-term efficacy of the vaccine.